Theoretical Study of the Electronic Spectrum of Disulfur Monoxide - Cobos, Carlos Jorge (2014)
The near ultraviolet-visible absorption spectrum of disulfur monoxide (S2O) has been theoreticallystudied by using the time-dependent density functional theory (TD-DFT) and the equation of motion coupled-cluster singles and doubles approach (EOM-CCSD) combined with the AUG-cc-PVQZ basis set. From this, analytical expressions for the absorption coefficient over the 250 ? 340 nm range are reported for the first time. The computed molecular structure and the vibrational frequencies for the ground and third electronically excited state S2O (C 1A′), responsible of the observed spectrum, are compared with available data